Comparison of interferon-γ release assays and tuberculin skin test in predicting active tuberculosis (TB) in children in the UK: a paediatric TB network study. Issue 3 (8th October 2009) - Bamford, Alasdair R J; Crook, Angela M; Clark, Julia E; Nademi, Zohreh; Dixon, Garth; Paton, James Y; Riddell, Anna; Drobniewski, Francis; Riordan, Andrew; Anderson, Suzanne T; Williams, Amanda; Walters, Sam; et al.
Abstract : Background: The value of interferon-γ release assays (IGRA) to diagnose active tuberculosis (TB) in children is not established, but these assays are being widely used for this purpose. The authors examined the sensitivity of commercially available IGRA to diagnose active TB in children in the UK compared with the tuberculin skin test (TST). Methods: The authors established a paediatric tuberculosis network and conducted a retrospective analysis of data from children investigated for active TB at six large UK paediatric centres. All centres had used TST and at least one of the commercially available IGRA (T-Spot.TB or Quantiferon-Gold in Tube) in the diagnostic work-up for active TB. Data were available from 333 children aged 2 months to 16 years. The authors measured the sensitivity of TST and IGRA in definite (culture confirmed) and probable TB in children, agreement between TST and either IGRA, and their combined sensitivity. Results: Of 333 children, 49 fulfilled the criteria of definite TB, and 146 had probable TB. Within the definite cohort, TST had a sensitivity of 82%, Quantiferon-Gold in tube (QFT-IT) had a sensitivity of 78% and T-Spot.TB of 66%. Neither IGRA performed significantly better than a TST with a cut-off of 15 mm. Combining the results of TST and IGRA increased the sensitivity to 96% for TST plus T-Spot.TB and 91% for TST plus QFG-IT in the definite TB cohort. Conclusions: A negative IGRA does not exclude active TB disease, but a combination of TST and IGRA increases the sensitivity for identifying children with active TB.